Adolescent morphine exposure induced long-term cognitive impairment and prefrontal neurostructural abnormality in adulthood in male mice - Ye Lu; Yijie Guo; Lulu Sun; Tong Liu; Ziqing Dong; Min Jia; Lixia Zhuo; Fangyuan Yin; Yongsheng Zhu; Xiancang Ma; Yunpeng Wang (Heliyon)
Opioids abuse in adolescence is becoming a pressing public health issue. While evidence suggests that exposure to opioids during adolescence leads to lasting alterations in brain development, the long-term cognitive implications in adulthood remain uncertain. We developed a male mouse model of adolescent morphine exposure and used the 5-choice serial reaction time task (5‐CSRTT), along with the open field, novel object recognition, Y maze and Barnes maze tests, to assess changes in cognitive behavior. We found that exposure to morphine during adolescence led to deficits in multidimensional cognitive functions in mice, including attention, information processing speed, and behavior inhibition. Notable, these impairments persisted into adulthood. Furthermore, the morphine-exposed mice exhibited decreased learning efficiency and spatial memory. Adolescent morphine exposure also induced significant and persistent morphological changes and synaptic abnormalities in medial prefrontal cortex (mPFC) neurons, which may be responsible for cognitive impairments in adulthood. Together, our study suggests that opioid exposure during adolescence profoundly affects cognitive development and emphasizes that opioid-induced disruption of neurons in adolescence may link mPFC-associated cognitive impairments in adulthood.